The VCU Pressure Ulcer Summit. Issue 4 (July 2015) - Brindle, C. Tod; Creehan, Sue; Black, Joyce; Zimmermann, Deb
<x xml:space="preserve">Abstract</x> This executive summary reports outcomes of an interprofessional collaboration between experts in pressure ulcer prevention, bedside clinicians, regulatory agencies, quality improvement, informatics experts, and professional nursing organizations. The goal of the collaboration was to develop a framework to assist facilities to operationalize best practice recommendations to sustain organizational culture change in hospital-acquired pressure ulcer prevention, to develop a hospital-acquired pressure ulcer severity score, and to address topics related to the unavoidable pressure ulcer.